Implementasi E-Arsip Pada Program Studi Teknik Informatika - Muhammad Dedi Irawan; Selli Aprilla Simargolang ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - The making of E-Archive Implementation in the Informatics Engineering Study Program is strived for perfection in the administration of archives which so far has not been integrated, and often the management of documents is still done manually. thus making work ineffective and efficient when faced with rapid information needs. The data collection method used is through observation and literature. Based on theoretical review, analysis and programming implementation used with PHP programming language with Notepad ++ editor and database using XAMPP, resulting in web-based e-archive programming, which can be used directly on Informatics Engineering Programs that can help process archiving organizers which is in accordance with the principle. so that later in the process of searching data and information archives become easier, and more accurate. Keywords - E-Archive, Implementation, Web